Screening Genes Promoting Exit from Naive Pluripotency Based on Genome-Scale CRISPR-Cas9 Knockout. (3rd February 2020) - Yang, Bin; Kuang, Junqi; Wu, Chuman; Zhou, Wenyi; Zhu, Shuoji; Jiang, Haodong; Zhai, Ziwei; Wu, Yue; Peng, Junwei; Liu, Nanbo; Hu, Haiyan; Ide, Nasser Moussa; et al.
Abstract : Two of the main problems of stem cell and regenerative medicine are the exit of pluripotency and differentiation to functional cells or tissues. The answer to these two problems holds great value in the clinical translation of stem cell as well as regenerative medicine research. Although piling researches have revealed the truth about pluripotency maintenance, the mechanisms underlying pluripotent cell self-renewal, proliferation, and differentiation into specific cell lineages or tissues are yet to be defined. To this end, we took full advantage of a novel technology, namely, the genome-scale CRISPR-Cas9 knockout (GeCKO). As an effective way of introducing targeted loss-of-function mutations at specific sites in the genome, GeCKO is able to screen in an unbiased manner for key genes that promote exit from pluripotency in mouse embryonic stem cells (mESCs) for the first time. In this study, we successfully established a model based on GeCKO to screen the key genes in pluripotency withdrawal. Our strategies included lentiviral package and infection technology, lenti-Cas9 gene knockout technology, shRNA gene knockdown technology, next-generation sequencing, model-based analysis of genome-scale CRISPR-Cas9 knockout (MAGeCK analysis), GO analysis, and other methods. Our findings provide a novel approach for large-scale screening of genes involved in pluripotency exit and offer an entry point for cell fate regulation research.